1988
DOI: 10.1103/physrevlett.61.2643
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the de Sitter precession of the Moon: A relativistic three-body effect

Abstract: We analyzed lunar laser-ranging data, accumulated between 1970 and 1986, to estimate the deviation of the precession of the Moon's orbit from the predictions of general relativity. We found no deviation from this predicted de Sitter precession rate of nearly 2 angular sec per century (sec/cy), to within our estimated standard error of 0.04 sec/cy. This standard error, 2% of the predicted effect, incorporates our assessment of the likely contributions of systematic errors, and is about threefold larger than the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(42 citation statements)
references
References 6 publications
2
40
0
Order By: Relevance
“…Although these are two independent effects in the sense that the latter requires rotation of the source of the gravitational field, it can be shown that in an appropriately chosen coordinate system [17], geodetic precession can be considered as due to a Lense-Thirring drag. A combined observable phenomenon of these two effects [18] occurs in the Earth-Moon system around the Sun through the precession of the Moon's perigee, which is detected by measuring the lunar orbit using laser ranging between stations on Earth and reflectors on the Moon's surface [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Although these are two independent effects in the sense that the latter requires rotation of the source of the gravitational field, it can be shown that in an appropriately chosen coordinate system [17], geodetic precession can be considered as due to a Lense-Thirring drag. A combined observable phenomenon of these two effects [18] occurs in the Earth-Moon system around the Sun through the precession of the Moon's perigee, which is detected by measuring the lunar orbit using laser ranging between stations on Earth and reflectors on the Moon's surface [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…PEP was designed not only to generate ephemerides of the Planets and Moon, but also to compare model with observations. One of the early uses of this software was the first measurement of the geodetic precession of the Moon [12]. The PEP software has enabled constraints on deviations from standard GR physics.…”
Section: Analysis Of Lunar Laser Ranging Datamentioning
confidence: 99%
“…Since 1969 LLR has supplied a lot of tests of General Relativity (GR): it has evaluated the Geodetic Precession [12], probed the weak and strong equivalence principle, determined the Parametrized Post Newtonian (PPN) parameter β and γ, addressed the time change of the gravitational constant (G) and 1/r 2 deviations. LLR has also provided important information on the composition and origin of the Moon through measurement of its rotations and tides.…”
Section: Introductionmentioning
confidence: 99%
“…h would equal zero if it were consistent with general relativity and unity if there were 100% difference from the prediction. From the set of 4 400 echo measurements, their analysis resulted in h = 0.019 ± 0.010 (Shapiro et al, 1988).…”
Section: Geodetic Precessionmentioning
confidence: 99%
“…This effect is referred to as geodetic precession. Shapiro et al (1988) mined the lunar laser ranging data collected over the period 1970-1986 from the retroreflectors on the Moon. A model of the Moon's motion consisted of two coupled sets of differential equations, one for its orbit and the other for its rotation.…”
Section: Geodetic Precessionmentioning
confidence: 99%